Retrieval and Storage of Research Information by the Post Graduate Students of Kerala Agricultural University - Shely Mary Koshy and Kishor Kumar N. (Indian Journal of Extension Education, 2015)
The retrieval and storage of research information is an important aspect when it comes to the post graduate students doingresearch. As far as agriculture students are considered, the research information retrieval is unavoidable for carrying outresearch works. Therefore, the study was conducted to find out the information retrieval behavior and storage ofinformation by the research graduates in Kerala Agricultural University. A questionnaire was prepared and distributedamong 30 post graduate students in various disciplines. The study revealed that more that more than 50 per cent of studentsretrieved information regularly. Seventy percentage of students accessed information to supplement their lecture notes.Fifty percentages of respondents utilized the library facilities more than once in a week. Internet was the source used toretrieve information by the respondents. Sixty percentage of respondents stored information occasionally and 76.6 percent of respondents had the habit of taking prints for storing the information.